A Preliminary Study Of Sexual Dimorphism Of Scapula By Computed Tomography In The Malaysian Population - Normaliza Omar; Siti Hanum Mohd Ali; Mohamed Swarhib Shafie; Nik Azuan Nik Ismail; Helmi Hadi; Faridah Mohd Nor (Innovare Academic Sciences Pvt. Ltd., 2024)
Objective: Sex estimation is one of the crucial steps for human identification, which is evident in cases of commingled, eroded, and/or missing remains. When pelvis or skull are unavailable, scapula has been used as an alternative bone for determining sex. Besides, the scapula was shown to be population-specific in several studies. Limited dry bone collections in Malaysia have led to various recommendations of virtual anthropology studies of bone in human identification. The aims of this study were to investigate the sexual dimorphism of the scapula using three-dimensional (3D) computed tomography (CT) imaging and to generate population-specific equations for sex determination in the Malaysian population.